Orange juice - Chessen, Betsey (New York : Scholastic Inc., 1998)
Photographs and simple text explain where orange juice comes from, with emphasis on the life cycle of the orange tree.
"Scholastic early childhood"--Includes index
Keywords: Oranges -- Juvenile literature; Orange juice -- Juvenile literature